Contextual Effect of - Rokhayati, Rokhayati; Salimo, Harsono; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: Iron deficiency can cause anemia which adversely affects children’s growth, especially in terms of achievement, quality of life, and performance as human resources in the future. Birth weight, exclusive breastfeeding complementary feeding (EBF-CF) have a direct relationship with the incidence of anemia in infants. The purpose of this study is to examine the factors that influence anemia in children under five at the Banguntapan II Bantul Health Center, Yogyakarta. Subjects and Method: The cross sectional study was conducted at 25 posyandu in the working area of Banguntapan II Bantul Health Center, Yogyakarta, Indonesia. A sample of 200 children aged 24